A Scoping Review of the Hospitality Industry and Tertiary Partnership to Prepare Work-ready Graduates - Hong Hanh Nguyen; Thirumanran Kailasam; Zilmiyah Kamble (Centre For Tourism Planning and Development, 2023)
This paper is a literature review, aimed to provide a comprehensive understanding of the collaboration between the hospitality higher educational sector and the industry to prepare work-ready graduates. A scoping review of 111 research papers published between April 2000 and September 2021 in reputable hospitality and tourism journals was conducted. Research revealed different perceptions between industry employers, educators, and students about competencies required of entry-level hospitality employees. Previous studies confirmed the positive impact of the industry-university collaboration on enhancing hospitality graduates’ employability. The work-integrated model has been widely implemented to develop hospitality students’ skill sets. Thus, hospitality higher education institutions need to adapt to the constantly changing business environment and present graduates with sufficient industry knowledge and skills. This study adds to the current literature on hospitality competencies expected from tertiary education graduates and highlights the appropriate methods to ensure effective industry-academia partnership. Generally, hospitality students and educators place more value on industry knowledge and technical skills. Hospitality tertiary educators should, thus, seek industry inputs more proactively to redesign their education programs, and industry professionals should engage and offer more support to higher education institutions to raise the quality of potential candidates.